The Effects of Profitability, Liquidity, Leverage, and Firm Size on Dividend Policy in Financial Companies in the Sub-Sector of Banking in the Indonesia Stock Exchange During the 2018-2022 Period - Sitinjak, Rizky; Hascaryani , Tyas Danarti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Dividend policy is a decision made by company management regarding the amount of profits that will be given to shareholders. Each company's dividend policy varies according to the company's financial condition, company management can distribute dividends or not provide dividends or retain profits. The aim of this research is to test and analyze the variables profitability, liquidity, leverage, and company size on dividend policy in financial companies in the banking subsector during 2018-2022. This research uses quantitative research and the data used in this research is secondary data. The sample in this study consisted of 11 companies. The analytical method used in this research is multiple regression analysis using panel data via Stata software. The results of this study indicate that profitability ratios, proxied by Return on Equity (ROE), and liquidity, proxied by the Current Ratio (CR), do not affect dividend policy. Leverage, proxied by the Debt to Equity Ratio (DER), has a negative effect, while company size, proxied by the natural logarithm of total assets, has a positive effect on dividend policy. Abstrak Tujuan penelitian ini adalah untuk menguji dan menganalisis variabel profitabilitas, likuiditas, leverage, dan ukuran perusahaan terhadap kebijakan dividen pada perusahaan keuangan subsektor perbankan selama tahun 2018-2022. Penelitian ini menggunakan penelitian kuantitatif dan data yang digunakan dalam penelitian ini yaitu data sekunder. Sampel pada penelitian ini berjumlah 11 perusahaan. Metode analisis yang digunakan pada penelitian ini adalah analisis regresi berganda dengan menggunakan data panel melalui software Stata. Hasil penelitian ini menunjukkan bahwa rasio profitabilitas yang diproksikan dengan Return on Equity (ROE), likuiditas yang diproksikan dengan Current Ratio (CR) tidak berpengaruh terhadap kebijakan dividen. leverage yang diproksikan dengan Debt to Equity (DER) berpengaruh negatif, serta ukuran perusahaan yang diproksikan dengan logaritma natural total aset berpengaruh positif terhadap kebijakan dividen.